Biochemistry : a very short introduction - Lorch, Mark (Oxford : Oxford University Press, 2021)
All living things are composed of cells, which have fundamentally the same chemistry. Biochemistry is the study of reactions within these cells, and the molecules that are created, manipulated, and destroyed as a result of them. This book discusses the key concepts of biochemistry, as well as the recent discoveries and innovations in the field.
Keywords: Biochemistry; Science